Is the cosmological particle production homogeneous? - Campos,M. de (2005)
Using a gauge-invariant formalism we find the density contrast equation in a cosmological scenario with particle production at the expenses of the gravitational field (open system cosmology). First, we find the modes for the density contrast considering that the particle production process participate of the inhomogeneities formation, and in a second phase the creation process mimics the inclusion of the a smooth L term , in the sense that it is not affects small deviations from homogeneity. The cosmic background has an accelerated regime, where an additional pressure due to the creation process is responsible for the cosmic acceleration. We study in this work if the creation process of particles in the cosmic fluid contributes to the inhomogeneities formation in an accelerated universe.